The Impact of Formalization and Centralization on Organizational Communication: A Study on a Highway Concessionaire in the Klang Valley, Malaysia - Md Nordin, Shahrina; Halib, Mohammed; Ghazali, Zulkipli (Queensland University of, 2009)
Abstract Organizational structure influences the flow of organizational communication and affects organizational efficiency and morale of personnel. The hierarchical nature of most organizations further complicates the communication flow among members. This study examines the impact of the organizational structure on the organizational communication pattern in a highway concessionaire company in the Klang Valley, Malaysia. Organizational structure is illustrated by the degree of formalization and centralization found in the organization. Organizational communication, a multidimensional construct, is analyzed through the satisfaction level in the communication climate, upward communication, downward communication, horizontal communication, organizational perspective, and organizational integration. Data on the study is principally gathered through the questionnaire-aided survey administered to employees at all levels in the company. The study revealed, among others, that centralization and formalization to have a positive impact on organizational communication satisfaction in the organization. The findings are thus in a contrary to a line of other research findings in the literature. The study therefore provides empirical evidence to the on-going debate on what type of organizational structure promotes communication satisfaction in the organization. The study concludes that there is no specific type of organizational structure that works best in every situation as it involves a variety of other variables.